War’s Toll of Italian Heritage: Unveiling Italy’s Post-war Reconstruction through Transnational Exhibitions - Jiang, Jiayao (Lo sguardo rinnovato, 2026)
In 1945, the National Association for Italian War-Damaged Monuments organized the Mostra d’Arte Italiana in Rome, framing heritage as vital for rebuilding post-war cultural identity. In 1946, in collaboration with the American Committee for the Restoration of Italian Monuments, War’s Toll of Italian Art was held at the Metropolitan Museum of Art in New York. These exhibitions––external to dominant narratives––remain under-explored. This article analyses them to reveal post-war Italian responses through a transnational lens. In the United States, the visual display of heritage destruction aimed to elicit emotional impact and drive fundraising, attributing universal value to the damaged Italian monuments. The article further explores the diplomatic value of these exhibitions, aligning with Italy’s shift from Fascist propaganda to cultural cooperation and peace building. In this vein, the article argues that these post-war exhibitions exemplify early transnational financial aid for heritage, evolving international conservation guidelines, and the reshaping of Italian national identity.